Eye Tracking Analysis in Reading Online Newspapers - Daniela Zambarbieri; Elena Carniglia; Carlo Robino (Bern Open Publishing, 2008)
Reading online newspapers is increasingly becoming more common, so that thousands of newspapers are published online today. Despite this development, there are many unanswered questions concerning subjects' behaviour during reading an online newspapers. Recording eye movements when a subject is navigating within a news website can provide quantitative and objective information on subject's behaviour and combined with other methodologies - usability testing, focus groups, log analysis - represents a powerful tool for improving news websites functionality, and by consequence their achievement among readers. Two Italian newspaper websites have been considered for the study described in this paper and the analysis has been focused on the exploration behaviour within the newspaper home page and the reading of article pages.